C(NTAR[IE KLASSY DETSKIH MUZYKALXNYH [KOL(B.(NaLXBOM SONATIN DLQ FORTEPIANO(B.s (NDLQ FORTEPIANO(B.(NWYPUSK (B3.(N~ASTX WTORAQ(B.s - (Nk(B.(Ns(B.(NsOROKIN(B.s (NrEDAKTOR(B-(NSOSTAWITELXs ((NmOSKWAs (NmUZYKAs, 1974)
(NsTAR[IE KLASSY DETSKIH MUZYKALXNYH [KOL(B.s
Keywords: (NFORTEPIANOs